2022
DOI: 10.1101/2022.07.01.497610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech-In-Noise Comprehension is Improved When Viewing a Deep-Neural-Network-Generated Talking Face

Abstract: Listening in a noisy environment is challenging, but many previous studies have demonstrated that comprehension of speech can be substantially improved by looking at the talker's face. We recently developed a deep neural network (DNN) based system that generates movies of a talking face from speech audio and a single face image. In this study, we aimed to quantify the benefits that such a system can bring to speech comprehension, especially in noise. The target speech audio was masked with signal to noise rati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This work was presented at the Association for Research in Otolaryngology Mid Winder Meeting (ARO MWM) 2021 ( Shan & Maddox, 2021 ). Research reported in this publication was supported by the National Institute for Deafness and Other Communication Disorders awarded to RKM (R00DC014288) and Augmented / Virtual Reality pilot grant awarded by the University of Rochester to RKM, CX, and ZD.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This work was presented at the Association for Research in Otolaryngology Mid Winder Meeting (ARO MWM) 2021 ( Shan & Maddox, 2021 ). Research reported in this publication was supported by the National Institute for Deafness and Other Communication Disorders awarded to RKM (R00DC014288) and Augmented / Virtual Reality pilot grant awarded by the University of Rochester to RKM, CX, and ZD.…”
Section: Acknowledgmentsmentioning
confidence: 99%